Cinematherapy Techniques: Guidance Effectiveness Increases Student Achievement Motives - agus sutardi (Universitas Pendidikan Indonesia, 2023)
This study aimed to establish the guidance with applied cinematherapy technique to increase achievement motivation at grade VIII. This research based on empirically study that more than 75% of students have low achievement motivation which has required guidance and counseling services to increase. This researchused quasiekperimental nonequivalen control group design. Study participantswere 35 students each in experimental and control group. Data was collected by instruments achievement motivationwith pair comparison and statistically processed through ANACOVA techniques. The results showed that guidance with applied cinematherapy technique used six films, namely Laskar Pelangi, Sang Pemimpi, Semesta Mendukung (Mestakung), Sang Pencerah, Negeri Lima Menara, dan Cahaya dari Timur (Beta Maluku) were effective increasing total score achievement motivation of the students. Specifically, there were four of ten aspects increase students achievement motivation, namely a negative reaction to failure, anxiety against the possibility of failure to achieve a goal, assistance or sympathetic to people who encourage and help direct individuals activities , and positive reaction to result achievement. Six aspects of the achievement motivation were not significantly affected by guidance with applied cinematherapy technique namely need to obtain the best results, anticipation of the goals to be achieved, efforts to result achievement, externalbarriers, internal barriers and the intensity of the desire to achieve best result.K